Time‐dependent antiarrhythmic effects of flecainide on induced atrial fibrillation in horses. (22nd August 2018) - Carstensen, Helena; Hesselkilde, Eva Z.; Fenner, Merle; Loft‐Andersen, Ameli V.; Flethøj, Mette; Kanters, Jørgen K.; Sattler, Stefan M.; Tfelt‐Hansen, Jacob; Pehrson, Steen; Jespersen, Thomas; Buhl, Rikke
Abstract : Background: Pharmacological treatment of atrial fibrillation (AF) in horses can be challenging because of low efficacy and adverse effects. Flecainide has been tested with variable efficacy. Objective: To test whether the efficacy of flecainide is dependent on AF duration. Animals: Nine Standardbred mares. Methods: Factorial study design. All horses were instrumented with a pacemaker and assigned to a control or an AF group. On day 0, all horses were in sinus rhythm and received 2 mg/kg flecainide IV. Atrial fibrillation subsequently was induced in the AF group by pacemaker stimulation. On days 3, 9, 27, and 55, flecainide was administered to all horses, regardless of heart rhythm. Results: All horses in AF cardioverted to sinus rhythm on days 3 and 9. On day 27, 5/6 horses cardioverted, whereas only 2/6 cardioverted on day 55. The time from the start of flecainide infusion to cardioversion (range, 3–185 min, log transformed) showed linear correlation with the cumulative duration of AF ( r 2  = .80, P  < .0001). Flecainide induced abnormal QRS complexes in 4/6 AF horses and 1/3 controls. A positive correlation was found between heart rate before flecainide infusion and number of abnormal QRS complexes (0.14, P  < .05). One horse suffered from cardiac arrest and died after flecainide infusion. Conclusions and Clinical Importance: Flecainide is effective for cardioversion of short‐term induced AF, but the effect decreases with AF duration. Controlling heart rate may minimize adverse effects caused by flecainide, but the drug should be used with great caution.